2014
DOI: 10.1021/jp506716d
|View full text |Cite
|
Sign up to set email alerts
|

Computational Investigation of Enthalpy–Entropy Compensation in Complexation of Glycoconjugated Bile Salts with β-Cyclodextrin and Analogs

Abstract: The inclusion complexes of glycoconjugated bile salts with β-cyclodextrin (β-CD) and 2-hydroxypropyl-β-cyclodextrins (HP-β-CD) in aqueous solution were investigated by molecular dynamics simulations to provide a molecular explanation of the experimentally observed destabilizing effect of the HP substituents. Good agreement with experimental data was found with respect to penetration depths of CDs. An increased degree of HP substitution (DS) resulted in an increased probability of blocking the cavity opening, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 61 publications
(82 reference statements)
1
14
2
Order By: Relevance
“…Both force field parameters allow the sugar ring to flip in the free states, and β -CD can easily adjust to an open cavity conformation when forming a complex with a guest. Therefore, unlike existing study showing that substituents attached to decorated β -CDs block a guest from binding, 70 the ring flipping itself in our study did not hinder guest binding. However, more flipped sugar rings modeled by GAFF-CD allow the formation of more H bonds between waters and β -CD and a more structured H-bond network as compared with conformations modeled by q4MD-CD.…”
Section: Discussioncontrasting
confidence: 91%
“…Both force field parameters allow the sugar ring to flip in the free states, and β -CD can easily adjust to an open cavity conformation when forming a complex with a guest. Therefore, unlike existing study showing that substituents attached to decorated β -CDs block a guest from binding, 70 the ring flipping itself in our study did not hinder guest binding. However, more flipped sugar rings modeled by GAFF-CD allow the formation of more H bonds between waters and β -CD and a more structured H-bond network as compared with conformations modeled by q4MD-CD.…”
Section: Discussioncontrasting
confidence: 91%
“…Cyclodextrins show promise for these separations as previous condensed phase studies have demonstrated their ability to form host-guest inclusion complexes with BAs. 3138 In these complexes, the aliphatic side chain of the BA can easily slip inside the hydrophobic cavity of the cyclodextrin, and the more bulky steroid portion fits between the hydrophilic exterior and hydrophobic interior. 3138 This hydrophobic cavity is created by the hydrogen atoms on H3 and H5 of the glucose moieties facing inward, with the hydrophilic rims being created from the primary and secondary hydroxyls (see the Supporting Information and refs 3941).…”
Section: Resultsmentioning
confidence: 99%
“…3138 In these complexes, the aliphatic side chain of the BA can easily slip inside the hydrophobic cavity of the cyclodextrin, and the more bulky steroid portion fits between the hydrophilic exterior and hydrophobic interior. 3138 This hydrophobic cavity is created by the hydrogen atoms on H3 and H5 of the glucose moieties facing inward, with the hydrophilic rims being created from the primary and secondary hydroxyls (see the Supporting Information and refs 3941). Based on this information, we hypothesized that the potential interactions between the cyclodextrin and tauro-BAs would result in gas phase host–guest inclusion ion complexes of varying size and shape after electrospray ionization (ESI), enabling separation with SLIM SUPER IM–MS.…”
Section: Resultsmentioning
confidence: 99%
“…This can partly explain why the HPβCD generally form weaker complexes than mβCD, since the hydroxyl group positioned on the propyl chain is hydrophilic and therefore disturbing the hydrophobic interactions between the preservative molecule and CD substituent. However, dehydration of the hydrophobic surface area in general have also been demonstrated to influence the interaction Tidemand et al, 2014), hence, some of the differences may also be due to the dissimilarity in energy from the dehydration of a hydrophobic moiety.…”
Section: Complexation Constantsmentioning
confidence: 99%